2021
DOI: 10.1016/j.ijso.2021.100397
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting 30-day postoperative complications after emergency surgery during the COVID-19 outbreak: A multicentre cohort study

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has influenced (surgical) care worldwide. Measures were taken to prioritize surgical care in order to maintain capacity for COVID-19 healthcare. However, the influence of these measures on emergency surgery is limited. Therefore, the aim of this study is to describe the trends in emergency surgery and determine the factors influencing the risk of postoperative complications during the first wave of the COVID-19 pandemic. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…It is such, that a trend towards higher numbers of emergency procedures during the SARS-CoV2 pandemic was observed. Comparing the two periods, a 10.2% increase in emergency operations was documented in the pandemic group which can be explained by the above-mentioned increased admission of emergency patients from smaller hospitals and is in line with findings by de Bock et al who reported an increase in the number of emergency surgeries during the COVID-19 outbreak and with Abduljawwad et al who reported no significant change in the prevalence of fusion procedures during the pandemic (7,17).…”
Section: Discussionsupporting
confidence: 87%
“…It is such, that a trend towards higher numbers of emergency procedures during the SARS-CoV2 pandemic was observed. Comparing the two periods, a 10.2% increase in emergency operations was documented in the pandemic group which can be explained by the above-mentioned increased admission of emergency patients from smaller hospitals and is in line with findings by de Bock et al who reported an increase in the number of emergency surgeries during the COVID-19 outbreak and with Abduljawwad et al who reported no significant change in the prevalence of fusion procedures during the pandemic (7,17).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our results may have been affected by this situation, and the worse outcomes in this group may be associated with worse patients' characteristics. Supporting the idea mentioned above, de Bock et al 16 found that increased age and higher ASA score were independent predictors of postoperative complications after emergency surgery during the outbreak, while the COVID-19 positivity was not. In another study, patients with severe acute respiratory syndrome who underwent elective or emergency surgery were divided into two groups according to the COVID-19 status, and the surgical outcomes were compared.…”
Section: Discussionmentioning
confidence: 73%
“…We saw that continuing surgery for gastrointestinal diseases can be safe and feasible, as long as strategies recommended by surgical societies to minimize the risk of perioperative SARS-CoV-2 transmission are followed. Data from the Netherlands also described that the performance of emergency general and oncological surgical procedures remained stable in a cohort of 1,399 patients ( 39 ). While data form an international multicenter study recommended to provide COVID-19–free surgical pathways (complete segregation of the operating theater, critical care, and inpatient ward areas) ( 40 ), there was also a study from within the NHS that only found a minimal impact of the pandemic on postoperative morbidity and mortality ( 41 ).…”
Section: Discussionmentioning
confidence: 99%